The Monocyte-Derived Exosomal CLMAT3 Activates the CtBP2-p300-NF-κB Transcriptional Complex to Induce Proinflammatory Cytokines in ALI - Zhi Chen; Wei-Hua Dong; Zhong-Min Qiu; Qiu-Gen Li (Elsevier, 2020)
Monocytes and macrophages are the two major cell types involved in innate immunity. Exosomes act as signaling molecules to regulate cell-to-cell communication by releasing proteins, mRNAs, microRNAs (miRNAs), and long noncoding RNAs (lncRNAs). However, it is still unclear whether monocyte-derived exosomes are involved in the communication between monocytes and macrophages. In this study, we analyzed the differentially expressed lncRNA profiles in monocytes isolated from blood samples of healthy controls and acute lung injury (ALI) patients. We focused our study on investigating the signaling downstream of CLMAT3 (colorectal liver metastasis-associated transcript 3), a lncRNA that regulated proinflammatory cytokine genes. We revealed that CLMAT3 specifically targeted CtBP2 (C-terminal binding protein 2) and repressed its expression. Elevated CtBP2 acted as a coactivator to assemble a transcriptional complex with histone acetyltransferase p300 and NF-κB (nuclear factor κB) subunits. In vitro coculture and in vivo injection of ALI monocyte-derived exosomes increased the production of proinflammatory cytokines. Importantly, the administration of two CtBP2 inhibitors, NSC95397 and MTOB, could significantly reverse CtBP2-mediated transactivation. Collectively, our results support a model in which monocyte-derived exosomal CLMAT3 activates the CtBP2-p300-NF-κB complex to induce proinflammatory cytokines, thus contributing to the pathogenesis of ALI.